The efficacy of generic imatinib in patients with chronic myeloid leukemia – a single center experience - Urošević, Ivana; Perčić, Ivanka; Dragičević Jojkić, Marina; Dokić, Marina; El Farra, Amir; Savić, Aleksandar; Milošević, Ivana; Vlaisavljević, Nada; Sekulić, Borivoj; Balint, Bela (Vojnosanitetski pregled, 2021)
Background/Aim. The treatment of chronic myeloid leukemia (CML) has changed dramatically with the advent of targeted therapies. This study aimed to assess the efficacy of generic imatinib in CML patients treated in our center. Methods. The study was retrospective. It included 101 patients diagnosed with CML – chronic phase (CP). The patients were divided into two groups. Group 1 included 55 patients initially treated with branded imatinib and then switched to generic imatinib. Group 2 consisted of 46 newly diagnosed patients who received only generic imatinib from the beginning of therapy. Results. The patients were treated with branded imatinib for the mean of 42 months (range 6–132 months) before switching to generic imatinib. Treatment with generic imatinib lasted for 25 months on average (range 3–66 months). A quarter of the patients from the group 1 lost their cytogenetic response after being switched to generic imatinib, but without signs of transformation to acute leukemia. The patients treated with branded imatinib had a significantly longer event-free survival (EFS) and failure-free survival (FFS) (log-rank p = 0.01 and p = 0.03, respectively). These results could have been influenced by frequent changes of the brand and dosage formulation of generic imatinib. Conclusions. Our study showed a significantly longer EFS and FFS in the patients who were initially treated with branded imatinib, compared to those treated with generic imatinib only. These results provide useful information, but have to be interpreted within the context of the crossover study.